Searching for new frontiers Hollywood films in the 1960s - Worland, Rick (Wiley, 2018)
"This book offers film students and general readers a survey of popular movies of the 1960s. The author explores the most important modes of filmmaking in times that were at once hopeful, exhilarating, and daunting. The text combines discussion of American social and political history and Hollywood industry changes with analysis of some of the era's most expressive movies" --Provided by publisher.